Pyogenic Liver Abscess with Delayed Presentation After Appendectomy - Piqueras, Ana I; Macia, Marian; Ibañez, Laura; Esteban, Maria Jesus (The Pediatric infectious disease journal, 2016)
Liver abscess is a serious condition that is uncommon in otherwise normal children. Predisposing factors include immunosuppression, surgery and travel to certain areas. We present a patient with liver abscess 4 months after appendectomy. In addition, we reviewed 7 cases of liver abscess that occurred in a 22-year period.